European Association of Urology Guidelines on Muscle-invasive and Metastatic Bladder Cancer: Summary of the 2023 Guidelines - Alfred Witjes, J.; Max Bruins, Harman; Carrión, Albert; Cathomas, Richard; Compérat, Eva; Efstathiou, Jason A.; Fietkau, Rainer; Gakis, Georgios; Lorch, Anja; Martini, Alberto; Mertens, Laura S.; Meijer, Richard P.; et al. (European urology, 2024)
The objective of the European Association of Urology guidelines is to provide practical evidence-based recommendations and consensus statements on the clinical management of urological conditions, with a focus on diagnosis and treatment. In this context the summary of the 2023 guideline on muscle-invasive and metastatic bladder cancer provides updated information on the diagnosis and treatment of this disease for incorporation in clinical practice. We present an overview of the updated 2023 European Association of Urology (EAU) guidelines for muscle-invasive and metastatic bladder cancer (MMIBC). To provide practical evidence-based recommendations and consensus statements on the clinical management of MMIBC with a focus on diagnosis and treatment. A broad and comprehensive scoping exercise covering all areas of the MMIBC guidelines has been performed annually since 2017. Searches cover the Medline, EMBASE, and Cochrane Libraries databases for yearly guideline updates. A level of evidence and strength of recommendation are assigned. The evidence cutoff date for the 2023 MIBC guidelines was May 4, 2022. Patients should be counselled regarding risk factors for bladder cancer. Pathologists should describe tumour and lymph nodes in detail, including the presence of histological subtypes. The importance of the presence or absence of urothelial carcinoma (UC) in the prostatic urethra is emphasised. Magnetic resonance imaging (MRI) of the bladder is superior to computed tomography (CT) for disease staging, specifically in differentiating T1 from T2 disease, and may lead to a change in treatment approach in patients at high risk of an invasive tumour. Imaging of the upper urinary tract, lymph nodes, and distant metastasis is performed with CT or MRI; the additional value of flurodeoxyglucose positron emission tomography/CT still needs to be determined. Frail and comorbid patients should be evaluated by a multidisciplinary team. Postoperative histology remains the most important prognostic variable, while circulating tumour DNA appears to be an interesting predictive marker. Neoadjuvant systemic therapy remains cisplatin-based. In motivated and selected women and men, sexual organ–preserving cystectomy results in better functional outcomes without compromising oncological outcomes. Robotic and open cystectomy have comparable outcomes and should be combined with (extended) lymph node dissection. The diversion type is an individual choice after taking patient and tumour characteristics into account. Radical cystectomy remains a highly complex procedure with considerable morbidity and risk of mortality, although lower rates are observed for higher hospital volumes (>20 cases/yr). With proper patient selection, trimodal therapy (chemoradiation) has comparable outcomes to radical cystectomy. Adjuvant chemotherapy after surgery improves disease-specific survival and overall survival (OS) in patients with high-risk disease who did not receive neoadjuvant treatment, and is strongly recommended. There is a weak recommendation for adjuvant nivolumab, as OS data are not yet available. Health-related quality of life should be assessed using validated questionnaires at baseline and after treatment. Surveillance is needed to monitor for recurrent cancer and functional outcomes. Recurrences detected on follow-up seem to have better prognosis than symptomatic recurrences. This summary of the 2023 EAU guidelines provides updated information on the diagnosis and treatment of MMIBC for incorporation into clinical practice. The European Association of Urology guidelines panel on muscle-invasive and metastatic bladder cancer has released an updated version of the guideline containing information on diagnosis and treatment of this disease. Recommendations are based on studies published up to May 4, 2022. Surgical removal of the bladder and bladder preservation are discussed, as well as updates on the use of chemotherapy and immunotherapy in localised and metastatic disease.